PENGARUH MODEL NUMBERED HEAD TOGETHER TERHADAP AKTIVITAS BELAJAR PENDIDIKAN KEWARGANEGARAAN - Rosyanti, Shinta Dewi; Adam, Fransisco; Yulita, Yulita (STKIP Melawi, 2019)
Abstract: This research aims to determine the effect of using the Numbered Head Together model on student learning activities in citizenship education in the third-grade students of SDN 01 Noyan. The research method used was a pre-experiment design with the research design used was one group pretest and posttest design. The data analyzed in this research are student learning activities before and after using the Numbered Head Together model. The results of pretest and posttest data analysis on student learning activities in citizenship education, it obtained that the pretest results was 52,81% with good categories, and the posttest results in ware 76,33% with very good categories. The results of the research showed a value difference between pretest and posttest of 23,43%. While the results of the hypothesis test are obtained t-count it 2,670 > t-table 2,064 then Ho is rejected and Ha is accepted, meaning that there is the influence pf the Numbered Head Together model on learning activities for citizenship education. Keywords: Numbered Head Together, Learning Activities. Abstrak: Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan model Numbere d Head Together terhadap aktivitas belajar siswa pada pendidikan kewarganegaraan di kelas III SDN 01 noyan. Metode penelitian yang digunakan adalah pre eksperiment design dengan rancangan penelitian yang digunakan adalah one group pretest posttest design. Data yang dianalisis dalam penelitian ini adalah aktivitas belajar siswa sebelum (pretest) dan sesudah (posttest) menggunakan model Numbered Head Together. Hasil analisis data pretest dan posttest terhadap aktivitas belajar siswa pada pendidikan kewarganegaraan diperoleh hasil pretest 52,81% dengan kategori baik, dan hasil posttest 76,25% dengan kategori sangat baik. Hasil penelitian tersebut menunjukan adanya selisih nilai antara pretest dan posttest 23,43%. Sedangkan hasil uji hipotesis didapat thitung 2,670> ttabel 2,064 maka H0 ditolak dan Ha diterima artinya ada pengaruh model Numbered Head Together terhadap aktivitas belajar pendidikan kewarganegaraanKata kunci: Numbered Head Together, Aktivitas Belajar